New Classes of Degenerate Unified Polynomials - Daniel Bedoya; Clemente Cesarano; Stiven Díaz; William Ramírez (Axioms, 2022)
In this paper, we introduce a class of new classes of degenerate unified polynomials and we show some algebraic and differential properties. This class includes the Appell-type classical polynomials and their most relevant generalizations. Most of the results are proved by using generating function methods and we illustrate our results with some examples.